Progressive osseous heteroplasia (POH) and other primary cutaneous ossifications. - Bufo, R.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2002)
The diagnosis of these disorders is initially done by neonatologists, pediatricans and pediatric dermatologists, who should be therefore aware of the problem. Although rare, these disorders, included progressive osseous heteroplasia (POH), are not exceptional. In fact, in our opinion many patients with POH are misdiagnosed. Moreover, some patients with osteomata cutis barely evident from a clinical point of view are never seen by expert physicians. (...)